Perancangan Dan Implementasi Aplikasi Berbasis Website Menggunakan Metode Prototype Untuk PT. HIS Food Industry: Optimalisasi Proses Pemesanan Dan Layanan Pelanggan - Donny Jaya Giri Pratama; Perani Rosyani (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
This research aims to design and implement a website-based application for PT. His Food Industry with a focus on optimizing the ordering process and customer service. The main problems identified were the slow ordering process and lack of efficiency in customer interactions, which had an impact on customer satisfaction and company performance. The method used in this study is the prototype method, which allows application development to be iterative and responsive to user needs. The initial prototype will be tested and evaluated to get feedback, so that the resulting application can meet user expectations. The expected result of this research is the creation of an intuitive and efficient application, able to speed up the ordering process, and improve the quality of customer service. With the implementation of this application, it is hoped that PT. His Food Industry can improve customer satisfaction and operational efficiency, supporting sustainable business growth.